(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
The article mainly discusses the ways to reduce seasonality in tourism. Because after the pandemic, tourism is undergoing a recovery process, and because of this, the tourist flow has started to increase even more. Therefore, opinions were expressed about ways to reduce the tourist season in the country, and if possible, to eliminate it altogether. The article mainly analyzed the introduction of new routes of tourism and the activities of spending their time meaningfully. In addition, the article is substantiated with examples from foreign experience in order to clarify scientific importance of the work. Alleviation of seasonality is important not only for representatives of the tourism industry, but also for other related enterprises.